A raid on the Red Sea : the Israeli capture of the Karine A - Gilboa, Amos (Potomac Books, an imprint of the University of Nebraska Press, 2021)
This is the thrilling real-life story of illegal gun-running in the Middle East and the intelligence and military operation that foiled it.